Tough and Highly Efficient Underwater Self‐Repairing Hydrogels for Soft Electronics. Issue 5 (4th March 2022) - Fu, Rumin; Guan, Youjun; Xiao, Cairong; Fan, Lei; Wang, Zhengao; Li, Yangfan; Yu, Peng; Tu, Lingjie; Tan, Guoxin; Zhai, Jinxia; Zhou, Lei; Ning, Chengyun
Abstract: The vulnerability of hydrogel electronic materials to mechanical damage due to their soft nature has necessitated the development of self‐repairing hydrogel electronics. However, the development of such material with underwater self‐repairing capability as well as excellent mechanical properties for application in aquatic environments is highly challenging and has not yet been fully realized. This study designs a tough and highly efficient underwater self‐repairing supramolecular hydrogel by synergistically combining weak hydrogen bonds (H‐bonds) and strong dipole–dipole interactions. The resultant hydrogel has high stretchability (up to 700%) and toughness (4.45 MJ m −3 ), and an almost 100% fast strain self‐recovery (10 min). The underwater healing process is rapid and autonomous (98% self‐repair efficiency after 1 h of healing). Supramolecular hydrogels can be developed as soft electronic sensors for physiological signal detection (gestures, breathing, microexpression, and vocalization) and real‐time underwater communication (Morse code). Importantly, the hydrogel sensor can function underwater after mechanical damage because of its highly efficient underwater self‐repairing capability. Abstract : Supramolecular hydrogels based on the synergistic effect of dipole–dipole interactions and hydrogen bonds have intrinsic properties of high‐efficiency self‐repairing underwater (within 1 h), high stretchability (up to 700%), and high toughness (≈4.45 MJ m −3 ). Besides, excellent physiological signal (gesture, microexpression, breathing, pronunciation, etc.) detection and real‐time communication (Morse code) performance endow them with potential as soft electronics.